2015
DOI: 10.1017/cem.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Health Care Use among Sociodemographic Groups of Children Presenting to Emergency Departments for Self-Harm in Alberta

Abstract: Objective: To examine sociodemographic variations among children <18 years in (1) rates of self-harm visits to emergency departments (EDs) and (2) physician follow-up after the selfharm visit in Alberta. Methods: A retrospective, population-based cohort (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) of ED visits for self-harm by individuals <18 years was conducted using administrative databases from Alberta, Canada. Individuals were grouped by First Nations status or type of health care premium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For pulmonary diseases, two studies found no difference in the quality of care for people with lower respiratory tract infections [ 55 , 115 ] and one study concluded that Indigenous patients with asthma or COPD were 55% less likely to see a specialist and 66% less likely to have a spirometry [ 96 ]. For injuries, one study found that Indigenous patients wait longer for their follow-up [ 106 ], are less likely to opt for palliative health care and undergo more surgeries [ 116 ]. Two studies showed a decreased chance for Indigenous patients to consult a specialist for their health problem [ 48 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For pulmonary diseases, two studies found no difference in the quality of care for people with lower respiratory tract infections [ 55 , 115 ] and one study concluded that Indigenous patients with asthma or COPD were 55% less likely to see a specialist and 66% less likely to have a spirometry [ 96 ]. For injuries, one study found that Indigenous patients wait longer for their follow-up [ 106 ], are less likely to opt for palliative health care and undergo more surgeries [ 116 ]. Two studies showed a decreased chance for Indigenous patients to consult a specialist for their health problem [ 48 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies did not present a comparison with non-Indigenous patients and conclusions could therefore not be drawn [102][103][104][105]. Finally, Newton found that Indigenous patients had double the rate of emergency visits for self-harm [106] and for psychiatric illnesses [107] when compared to non-Indigenous patients.…”
Section: Emergency Department Visit Ratesmentioning
confidence: 99%